INSTITUSIONALISASI REFORMASI BIROKRASI (STUDI KASUS PADA BADAN PUSAT STATISTIK) - Vony Wahyunurani; Made Sudarma; Bambang Hariadi (Jurnal Akuntansi Aktual, 2017)
This study aims to describe the institutionalization of Bureaucratic Reforms carried out by Badan Pusat Statistik. Case study method by institutional theory is useful to explain various types of pressure occurs in institutionalization process of bureaucratic reform. This – which is isomorphism and implemented through coercive pressure – has not been able to realize a fundamental change. This triggers organization to maximize institutionalization through STATCAP-CERDAS Program through mimetic and normative pressures.Keywords: bureaucratic reforms, institutionalism, isomophism